Leishmaniose Tegumentar Americana na região Centro-Oeste: avaliação de dados clínicos, epidemiológicos, laboratoriais e moleculares - Balian, Rosana Pereira Morais (2014)
Protozoa of the genus Leishmania, which affects the skin and/or mucous membranes, cause American Cutaneous Leishmaniasis (ACL). It is an endemic zoonosis whose numbers of cases in the Brazil Midwest region are growing. In the Goiás state, 2798 ACL cases were been reported between 2007 and 2013. In the present study, our proposal was to investigate the epidemiological and molecular characteristics of ACL patients attended at the ambulatory of the Hospital Anuar Auad in the period 2000 at 2006 and identify the species of Leishmania sp. The study included 152 patients with ACL, 124 were from of the state of Goiás and 28 at Mato Grosso, aged between 6-79 years, and center and thirteen these individuals were male. For diagnosis, clinical, epidemiological and laboratory data were collected, such as direct examination (ED), histopathology (AH), Montenegro skin test (MST), indirect immunofluorescence (IIF). ELISA using crude extract of L. (Viannia) braziliensis was performing. Characterization of Leishmania species was carried out by polymerase chain reaction (PCR). The positivity of ED, AH, MST, IIF and ELISA was 70.6%, 80.9%, 68.9%, 44.2% and 73.0%, respectively. Specific IgG to L. (V.) braziliensis were detecting in 84.7% of patients with mucosal leishmaniasis (ML), significantly higher than those found in patients with cutaneous leishmaniasis (CL), which was 69.0% (p < 0.05). Detection of IgG before and after treatment was performed using ELISA and was observed a statistically significant difference only in samples obtained from patients with CL after 6 and 18 months of treatment. The data serological monitoring of patients with ACL before and after treatment indicates that the total IgG levels tend to decrease after 6 months of treatment. PCR was performed on 69 samples obtained from scraping the edge of lesions of patients with ATL, these, 62 (89.8%) were positive, 53 patients with LC and 9 patients with ML. The samples were characterized by PCR as L. (V.) braziliensis (93.5%) and L. (L.) amazonensis (6.5%). It was found that 25.8% of cases of leishmaniasis in the state of Goiás occurred in Campestre, Goiânia, Aparecida de Goiânia and Niquelândia. By analyzing the frequency of cases of ATL over the months during the years analyzed, it was observed that there was a distribution of ACL in all seasons from 2000 to 2006, with a larger number of cases in winter. PCR represents important and powerful tool in the diagnosis and species identification in ACL in endemic areas. ACL controlling in endemic areas is difficult and requires an accurate idea of its epidemiology.